MEMBANGUN BRANDING TEBA MAJALANGU SEBAGAI DESTINASI WISATA EDUKASI DAN REKREASI - Bagus Bayu Andhika Putra; I Komang Winada; I Komang Adi Ardika; I Made Pande Sedana Merta; I Made Supriana; Yoga, Gede Agus Dian Maha (Dharma Bhakti, 2025)
Developing effective branding is very important in creating an attractive and memorable tourist destination identity. This research aims to build Teba Majalangu's branding as an educational and recreational tourism destination that can attract visitors. The method used in this research is a survei and content analysis obtained from various social media platforms to understand people's perceptions and expectations of Teba Majalangu. Surveis were conducted to collect data about visitor preferences, while content analysis focused on evaluating the images and messages conveyed via social media regarding this destination. The results of this research show that branding is relevant and effective for promoting Teba Majalangu as a tourist destination that combines educational value with entertainment, as well as increasing tourist visits. Apart from that, this research also provides insight into the potential use of social media in strengthening the image and attractiveness of tourist destinations.